2020
DOI: 10.3390/brainsci10050310
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation to Facilitate Lower Limb Recovery Following Stroke: Current Evidence and Future Directions

Abstract: Stroke remains a global leading cause of disability. Novel treatment approaches are required to alleviate impairment and promote greater functional recovery. One potential candidate is transcranial direct current stimulation (tDCS), which is thought to non-invasively promote neuroplasticity within the human cortex by transiently altering the resting membrane potential of cortical neurons. To date, much work involving tDCS has focused on upper limb recovery following stroke. However, lower limb rehabilitation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
(111 reference statements)
0
11
0
2
Order By: Relevance
“…In another study, the authors applied multi-channel electrodes (Otal et al, 2016 ). A computational modeling study that compared electrode placements targeting M1 (i.e., electrode placements for all studies included in this meta-analysis) and the cerebellum found that cerebellar stimulation produced substantially higher electric field strengths in the target area compared to M1 stimulation, suggesting that the cerebellum may indeed be a suitable target for tDCS (Gowan and Hordacre, 2020 ). Future tDCS studies should consider these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the authors applied multi-channel electrodes (Otal et al, 2016 ). A computational modeling study that compared electrode placements targeting M1 (i.e., electrode placements for all studies included in this meta-analysis) and the cerebellum found that cerebellar stimulation produced substantially higher electric field strengths in the target area compared to M1 stimulation, suggesting that the cerebellum may indeed be a suitable target for tDCS (Gowan and Hordacre, 2020 ). Future tDCS studies should consider these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as an example of rehabilitation in patients with lower limb motor paralysis, some studies have shown the effectiveness of non-invasive brain stimulation (NIBS), such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS). Multiple meta-analyses and systematic reviews have examined the efficacy of tDCS, rTMS, or spinal direct current stimulation on lower limb motor function related to gait and balance function in patients with stroke or SCI (Chieffo et al, 2016 ; Fleming et al, 2017 ; Li et al, 2018 ; Ghayour-Najafabadi et al, 2019 ; Tung et al, 2019 ; Abualait and Ibrahim, 2020 ; Elsner et al, 2020 ; Gowan and Hordacre, 2020 ). Although most meta-analyses have demonstrated the effectiveness of NIBS, some have shown limited effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The first use of tDCS to enhance stroke recovery in the acute phase (30 min after stroke induction) was in 2013, and the authors showed reduced lesion volume and improved neurological-severity scores in mice following cathodal stimulation to the sensorimotor cortex (Peruzzotti-Jametti et al, 2013). Anodal tDCS over the target brain area and the cathode placed over the contralateral region, has proved effective in improving both upper and lower limb impairments in stroke patients, as well as anxiety and depressive symptoms (Fusco et al, 2014;Allman et al, 2016;Fleming et al, 2017;Bornheim et al, 2020;Gowan and Hordacre, 2020). Beta coherence between the ipsilesional motor cortex and other brain regions increased in stroke patients who received cathodal tDCS over the contralesional primary motor cortex in the first 4 weeks after stroke, and this increase correlated with improved motor function (Nicolo et al, 2018).…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…This cortical area is located in the medial part of the precentral gyrus deep within the interhemispheric ssure. Targeted application of tDCS to this area is more challenging than targeting the upper limbs [22]. High-de nition transcranial direct current stimulation (HD-tDCS) with smaller "high-de nition" electrodes has been proposed to improve the focus of the stimulation in the target area [23].…”
Section: Introductionmentioning
confidence: 99%